Immune response to the src gene product in mice bearing tumors induced by injection of avian sarcoma virus-transformed mouse cells. - Parsons, S J (1979)
A single subcutaneous injection of 10(7) live cells of the highly tumorigenic avian sarcoma virus (Schmidt-Ruppin strain, subgroup D)-transformed BALB/c line into BALB/c mice resulted in the production of an antiserum specific for the avian sarcoma virus gene product pp60src. All sera taken from mice 3 weeks after injection of tumor cells contained antibodies to pp60src. Immunoprecipitation experiments showed that all sera precipitated pp60src from Schmidt-Ruppin-infected chicken cells, but only a portion of these sera precipitated pp60src from chicken cells infected with other strains of avian sarcoma virus, i.e., Prague and Bratislava-77. Analysis of the cross-reactivity patterns of these antisera demonstrated a minimum of three to four antigenic determinants on pp60src. The findings reported here should facilitate the production of monoclonal antibodies to pp60src, which in turn will provide highly specific probes for further investigations into the structure and function of this protein.